2014
DOI: 10.1097/aog.0000000000000285
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Glyburide Compared With Insulin Use for Gestational Diabetes Treatment in the United States, 2000–2011

Abstract: Objective To describe trends and identify factors associated with choice of pharmacotherapy for gestational diabetes (GDM) from 2000–2011 using a healthcare claims database. Methods This was a retrospective cohort study of a large nationwide population of commercially insured women with GDM and pharmacy claims for glyburide or insulin prior to delivery, 2000–2011. We excluded women younger than 15 years or older than 50 years, those with prior type 2 diabetes, or those who had multiple gestations. We estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 25 publications
4
40
1
Order By: Relevance
“…With the changing prevalence of GDM, trends in prescription of glucose-lowering agents for patients with GDM have also changed. A retrospective cohort study of the nationwide population in the U.S., performed in 2000–2011, showed that glyburide replaced insulin as the most common pharmacotherapy for GDM [ 5 ], and glyburide use increased from 7.4% to 64.5% over the past decade [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the changing prevalence of GDM, trends in prescription of glucose-lowering agents for patients with GDM have also changed. A retrospective cohort study of the nationwide population in the U.S., performed in 2000–2011, showed that glyburide replaced insulin as the most common pharmacotherapy for GDM [ 5 ], and glyburide use increased from 7.4% to 64.5% over the past decade [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…US guidelines still maintain that insulin is the only safe choice for pharmaceutical treatment of diabetes in pregnancy, but the American Diabetes Association recommendations state that metformin and glibenclamide can be used with the caveat of there being no longer term follow-up on the children exposed to these medications in pregnancy (G12 and G14). A previous study in the US MarketScan database showed that glibenclamide use increased from 2000 to 2011 to replace insulin as the most common GDM treatment from 2007 onward 31. Our study includes US MarketScan data from 2012 to 2015 and shows that glibenclamide continues to be the most commonly used ADM for GDM treatment, and overall, metformin is the most commonly used ADM in this population of privately insured pregnant women.…”
Section: Discussionmentioning
confidence: 71%
“…Glyburide is an oral hypoglycemic drug that is prescribed more commonly for the treatment of GDM than before [3]. Though glyburide exhibits nearly comparable efficacy to insulin, the incidence rates of adverse fetal effects associated with glyburide verses insulin therapy, such as neonatal hypoglycemia and large for gestational age infants, are conflicting [48].…”
Section: Introductionmentioning
confidence: 99%